Pengembangan Pengembangan Bahan Ajar Akhlak Berbasis Make a Match Kelas XI di MA Al Bairuny Jombang - Laili, Nur Hidayatul; Pertiwi, Novia Ayu Sekar; Ashoumi, Hilyah (JoEMS (Journal of Education and Management Studies), 2024)
This research aims to develop Moral teaching materials based on the Make a Match learning model for class XI at MA Al Bairuny and evaluate the level of validity and feasibility. Apart from that, this research also aims to assess students' responses to the teaching materials developed. It is hoped that the results of this research can provide benefits in improving the quality of Moral learning for students, teachers, schools and researchers. The method used in this research is the ADDIE development model, which includes the steps of Analysis, Design, Development, Implementation, and Evaluation. The data collection instruments used were validation questionnaires and student response questionnaires. Data analysis techniques include validation questionnaire data analysis and user response data analysis. Based on the research conducted, the results show that the Make a Match-based Moral teaching materials at MA Al Bairuny received a percentage of scores from validators of 87.1% and 77.7%, which shows that these teaching materials are valid and very suitable for use. Apart from that, students' responses to the teaching materials also showed positive results. The conclusion of this research is that Make a Match-based Moral teaching materials are effective and suitable for use in the learning process at MA Al Bairuny Jombang..